Real Life Project Based Physics Teaching Related to Majors (“RPPTM”) Teaching Model for Health Science Undergraduates - Sharma, Dipti; Farah, Kimberly (European Journal of Applied Sciences, 2021)
In this article, we describe a teaching model that was developed for an introductory-level physics course for allied health students. The aim of this model is to encourage and to engage them in the creative process of learning by posing collective challenges related to real world problems. The culmination of the course involves designing a project working with data analysis software and laboratory techniques related to real world applications. Throughout the course, students experience inquiry-based learning, open ended questions, and independent research. The model encourages students to work beyond the physics classroom to engage in questions and research related to their majors. We describe the motivation for the model and the implementation and outcomes of the model, report on impact on students, and suggest ways in which creativity can be encouraged in all science courses.